2016
DOI: 10.1103/physrevb.93.064420
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Gd polarization on the large magnetocaloric effect ofGdCrO4in a broad temperature range

Abstract: The ferromagnetic zircon-type phase of GdCrO 4 presents high values for the magnetocaloric (MC) parameters. This compound has large isothermal entropy changes S T under the magnetic field action in a wide temperature range, from 5 to 35 K, reaching a maximum | S T | = 29.0 ± 0.1 J/kg K at 22 K, for a field increment B = 9 T. It orders ferromagnetically at T C = 21.3 K via the Cr-Cr exchange interaction and shows a second transition at 4.8 K due to the ordering of the Gd sublattice. The large MC effect is enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 33 publications
4
33
0
Order By: Relevance
“…The present study on GdVO 4 also sheds light on the analysis of the GdCrO 4 data reported in Ref. [8]. There, the Gd-Gd exchange interaction was neglected because of the much stronger and dominating Gd-Cr and Cr-Cr interactions.…”
Section: Introductionsupporting
confidence: 54%
See 3 more Smart Citations
“…The present study on GdVO 4 also sheds light on the analysis of the GdCrO 4 data reported in Ref. [8]. There, the Gd-Gd exchange interaction was neglected because of the much stronger and dominating Gd-Cr and Cr-Cr interactions.…”
Section: Introductionsupporting
confidence: 54%
“…Hereafter, we focus on RVO 4 , where R is either Gd or Nd. Gadolinium orthovanadate is somewhat similar to GdCrO 4 and GdPO 4 alloys previously studied [8][9][10]. However, it significantly differs from GdPO 4 since GdVO 4 has a more symmetric, nonfrustrating, zircon (ZrSiO 4 -type) structure, in which each Gd 3+ ion has four nearest neighbors of the same type at 3.93Å, forming a distorted diamond lattice shown below.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…The MCE has been explored in many insulating oxides 913 , which can be easily manufactured on account of the chemical stability along with the avoidance of the refrigeration inefficiency driven by eddy current losses. Recently, the giant cryogenic MCE was discovered in several transition metal oxides such as Dy 2 CoMnO 6 10 (Δ S M  = 9.3 J/kg·K for Δ H  = 0–7 T), HoMnO 3 11 (Δ S M  = 13.1 J/kg·K for Δ H  = 0–7 T)., GdCrO 4 12 (Δ S M  = 29.0 J/kg·K for Δ H  = 0–9 T), and HoCrO 4 13 (Δ S M  = 31.0 J/kg·K for Δ H  = 0–8 T). However, most of the studies were performed on polycrystalline forms, preventing detailed characterization of the intrinsic properties of the giant MCE associated with magnetic and crystalline anisotropy.…”
Section: Introductionmentioning
confidence: 99%